Synthesis, biological evaluation and molecular docking of methoxy n-phenylpyrazoline derivatives as anticancer agents - Wahyuningsih, Tutik Dwi; Setiawati, Setiawati; Suma, Artania Adnin Tri; Stansyah, Yoeretisa Miggia; Astuti, Endang (Pakistan Journal of Pharmaceutical Sciences, 2022)
This research aims to synthesize some N-phenylpyrazoline derivatives with methoxy substituents and study their activity as potent anticancer agents as well as their interaction with the EGFR receptor on cancer cells. The synthesis of N-phenylpyrazolines was carried out via cyclocondensation reaction of chalcones and phenylhydrazine. All products were elucidated using GC-MS, FT-IR, 1H- and 13C-NMR spectrometers. The cytotoxicity evaluation was performed against cancer cell lines (HeLa, MCF-7, T47D, WiDr) and normal cell lines (Vero) using MTT assays. A molecular docking study of pyrazolines was conducted toward EGFR protein as a receptor. Cyclocondensation reactions yielded N-phenylpyrazolines in 63-91%. The presence of methoxy substituents on synthesized pyrazolines enhanced their potency as an anticancer agent. The best pyrazolines with high cytotoxicity and selectivity are compound 2e against HeLa cell line, 2d against WiDr cell line and 2f against MCF-7 cell line. Compound 2g is the most promising anticancer agent with a broad spectrum activity toward several cancer cell lines. A molecular docking study showed that the binding energy value of compound 2g with EGFR receptor is -8.4 kcal/mol and has interaction with Met769 residue. This study presented a convenient method for preparing N-phenylpyrazoline derivatives as promising anticancer candidates.